ISSUES OF UPBRINGING IN UZBEK FAMILIES - Imomqulova, Fotima (Журнал Педагогики и психологии в современном образовании, 2021)
The article discusses the role of spiritual factors in productive lifefamilies. Special attention is paid to the description of the construct "spiritual abilities". The article analyzes the influence of the spiritual and moral aspect of value orientations and motivation on the satisfaction withmarriage and the success of family life. It is shown that family well-beingcontribute to: spiritual and moral motives of marriage, spiritual value orientations related to the awareness of life meanings, self-improvement,altruism. The importance for the productive life of the spiritual family is notedabilities and the underlying spiritual orientation of the individual